The rapid decay phase of the afterglow as the signature of the Blandford–Znajek mechanism. Issue 4 (10th December 2015) - Nathanail, A.; Strantzalis, A.; Contopoulos, I.
Abstract: Gamma-ray bursts (GRBs) are believed to be powered by the electromagnetic extraction of spin energy from a black hole endowed with a magnetic field supported by electric currents in a surrounding disc (Blandford & Znajek). A generic feature of this mechanism is that, under certain fairly general assumptions, the energy loss rate decays exponentially. In this work, we are looking precisely for such exponential decay in the light curves of long-duration GRBs observed with the X-ray telescope (XRT) instrument on the Swift satellite. We found out that almost 30 per cent of XRT light curves show such behaviour before they reach the afterglow plateau. According to Blandford & Znajek, the duration of the burst depends on the magnetic flux accumulated on the event horizon. This allows us to estimate the surface magnetic field of a possible progenitor. Our estimations are consistent with magnetic fields observed in Wolf–Rayet stars.